The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1007/978-1-4899-0117-0_49
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Taurine on Human Fetal Neuron Cells: Proliferation and Differentiation

Abstract: The purpose of this study was to investigate the effect of taurine on human fetal brain neuron cell proliferation and differentiation using a glial-free, pure cerebral neuronal culture grown in a serum-free environment. We found that taurine was necessary for neuronal survival and neurite extension. Taurine, on the other hand, has a trophic effect on the human fetal brain cell, promoting both proliferation and differentiation. Results showed that DNA synthesis of the neurons was increased in a dose-dependent m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
27
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(32 citation statements)
references
References 9 publications
4
27
0
1
Order By: Relevance
“…2), which agreed with the earlier reports (Chen et al 1997;Shivaraj et al 2012). In their studies, DNA synthesis of human fetal neuron cells was increased in a dose-dependent manner when neurons were cultured in the medium containing taurine at 100 to 6,400 µM (12.515 to 800.96 µg/ml) (Chen et al 1997). And taurine at appropriate concentrations ranging from 100 µM (12.515 µg/ml) to 500 µM (62.575 µg/ml) stimulated the proliferation of P5 NPCs (neural progenitor cell) for 2 days (Shivaraj et al 2012).…”
supporting
confidence: 93%
See 1 more Smart Citation
“…2), which agreed with the earlier reports (Chen et al 1997;Shivaraj et al 2012). In their studies, DNA synthesis of human fetal neuron cells was increased in a dose-dependent manner when neurons were cultured in the medium containing taurine at 100 to 6,400 µM (12.515 to 800.96 µg/ml) (Chen et al 1997). And taurine at appropriate concentrations ranging from 100 µM (12.515 µg/ml) to 500 µM (62.575 µg/ml) stimulated the proliferation of P5 NPCs (neural progenitor cell) for 2 days (Shivaraj et al 2012).…”
supporting
confidence: 93%
“…2), which agreed with the earlier reports (Chen et al 1997;Shivaraj et al 2012). In their studies, DNA synthesis of human fetal neuron cells was increased in a dose-dependent manner when neurons were cultured in the medium containing taurine at 100 to 6,400 µM (12.515 to 800.96 µg/ml) (Chen et al 1997).…”
supporting
confidence: 89%
“…Taurine increases cell proliferation in human fetal neurons [17], in rabbit and human retinal pigment epithelium [18] and in human osteoblasts [19]. Taurine reverses the antiproliferative effect of high glucose and glycosylation end products in the glomerular mesangial and in renal tubule epithelial cells, two cell types which play a central role in the pathogenesis of diabetic nephropathy [20,21].…”
Section: Taurine and Cell Proliferationmentioning
confidence: 99%
“…Studies in monkeys fed formulas without taurine showed a similar defective maturation of the visual cortex (Neuringer et al, 1990). In vitro, defective migration in taurine-deficient cultured brain cells, and effects of taurine increasing or restoring cell proliferation of human fetal neurons have been documented (Maar et al, 1995;Chen et al, 1998). Altogether, these findings point to a possible effect of taurine in some steps of brain ontogeny, as a trophic factor and/or a protective factor necessary for optimal maturation of brain cells.…”
mentioning
confidence: 94%